Developmental toxicity, oxidative stress and immunotoxicity induced by three strobilurins (pyraclostrobin, trifloxystrobin and picoxystrobin) in zebrafish embryos. (September 2018) - Li, Hui; Cao, Fangjie; Zhao, Feng; Yang, Yang; Teng, Miaomiao; Wang, Chengju; Qiu, Lihong
Abstract: Strobilurins is the most widely used class of fungicides, but is reported highly toxic to some aquatic organisms. In this study, zebrafish embryos were exposed to a range concentrations of three strobilurins (pyraclostrobin, trifloxystrobin and picoxystrobin) for 96 h post-fertilization (hpf) to assess their aquatic toxicity. The 96-h LC50 values of pyraclostrobin, trifloxystrobin and picoxystrobin to embryos were 61, 55, 86 μg/L, respectively. A series of symptoms were observed in developmental embryos during acute exposure, including decreased heartbeat, hatching inhibition, growth regression, and morphological deformities. Moreover, the three fungicides induced oxidative stress in embryos through increasing reactive oxygen species (ROS) and malonaldehyde (MDA) contents, inhibiting superoxide dismutase (SOD) activity and glutathione (GSH) content as well as differently changing catalase (CAT) activity and mRNA levels of genes related to antioxidant system ( Mn-sod, Cu/Zn-sod, Cat, Nrf2, Ucp2 and Bcl2 ). In addition, exposure to the three strobilurins resulted in significant upregulation of IFN and CC-chem as well as differently changed expressions of TNFa, IL-1b, C1C and IL-8, which related to the innate immune system, suggesting that these fungicides caused immunotoxicity during zebrafish embryo development. The different response of enzymes and genes in embryos exposed to the three fungicides might be the cause that leads to the difference of their toxicity. This work made a comparison of the toxicity of three strobilurins to zebrafish embryos on multi-levels and would provide a better understanding of the toxic effects of strobilurins on aquatic organisms. Highlights: Pyraclostrobin,  trifloxystrobin,  picoxystrobin were highly toxic to zebrafish embryos. The three strobilurins caused severe developmental abnormalities of zebrafish embryos. The three strobilurins induced oxidative stress in embryos. The transcription of immune related genes of embryos changed by these strobilurins.